Behaviors That Improve Salespeople’s Performance and Handover Difficulties: Analysis from the Perspective of Tacit Knowledge - Takaya TOYOZUMI; Hidenori SATO (AAOS Transactions)
Handing over work is one of the concrete acts of knowledge transfer. However, in business, there are many cases where handover is not carried out smoothly. One of the reasons for this is that tacit knowledge on the part of the person handing over the work makes it difficult for the successor to put the knowledge into writing, even though it is necessary for the successor, and this is thought to hinder the transfer of knowledge in the execution of the work. The inability to pass on tacit knowledge is a challenge for organizations, especially when the performance of those who possess a large amount of tacit knowledge is high. Based on this issue, this study uses statistical analysis methods to show the relationship between sales behavior and tacit knowledge, and between sales performance and tacit knowledge, using corporate salespeople as the research subjects. In conclusion, we found a negative relationship between tacit knowledge and sales performance, and a negative relationship between sales behavior and sales autonomy, which is associated with tacit knowledge. Salespeople with high sales autonomy tend to have low tacit knowledge, which facilitates handover.